2020
DOI: 10.1029/2020jb019415
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Boundary Diffusion Creep of Olivine: 1. Experiments at 1 atm

Abstract: We conducted one‐atmosphere uniaxial compression experiments on fine‐grained (~1 μm) Fe‐bearing olivine (Mg1.8Fe0.2SiO4) aggregates that were variably doped with CaO ± Al2O3. We identified power‐law interface‐controlled creep at low stresses and grain‐boundary diffusion creep at high stresses, which operate as mutually coupled, that is, sequential processes. We established constitutive equations for interface‐controlled creep and diffusion creep of undoped olivine and used the combined rate equation as a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(96 citation statements)
references
References 74 publications
(238 reference statements)
18
68
0
Order By: Relevance
“…Thus, we consider the shear viscosity ( η=σ/)(3trueε̇) of the upper mantle based on Equation 6, in which an activation volume ( V ) is added and the temperature is replaced with the geotherm ( T geo ): η=d33Adiffχdiffexp)(Qdiff+italicPVnormalRTgeo, where χdiff=13.5emat1emTgeo/Ts0.92, χdiff=exp][ΔQnormalRTs·)(1Tgeo/Ts10.920.25emat0.25emTgeo/Ts>0.92. We used 4 cm 3 /mol for V , which was determined by Si grain‐boundary self‐diffusion experiments on our synthesized Fe‐free olivine aggregates at pressures ranging from 0.1 MPa to 13 GPa (Fei et al, 2016). In Part 1 of this study (Yabe et al, 2020), we showed good reproductions of our obtained creep rates for Fe‐free and Fe‐bearing olivine with their reported diffusivities (Figure 14 in Yabe et al, 2020). As seen in Equations 20a–20c, grain size, temperature ( T geo ), and normalized temperature ( T geo / T s ) are the primary factors controlling viscosity.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Thus, we consider the shear viscosity ( η=σ/)(3trueε̇) of the upper mantle based on Equation 6, in which an activation volume ( V ) is added and the temperature is replaced with the geotherm ( T geo ): η=d33Adiffχdiffexp)(Qdiff+italicPVnormalRTgeo, where χdiff=13.5emat1emTgeo/Ts0.92, χdiff=exp][ΔQnormalRTs·)(1Tgeo/Ts10.920.25emat0.25emTgeo/Ts>0.92. We used 4 cm 3 /mol for V , which was determined by Si grain‐boundary self‐diffusion experiments on our synthesized Fe‐free olivine aggregates at pressures ranging from 0.1 MPa to 13 GPa (Fei et al, 2016). In Part 1 of this study (Yabe et al, 2020), we showed good reproductions of our obtained creep rates for Fe‐free and Fe‐bearing olivine with their reported diffusivities (Figure 14 in Yabe et al, 2020). As seen in Equations 20a–20c, grain size, temperature ( T geo ), and normalized temperature ( T geo / T s ) are the primary factors controlling viscosity.…”
Section: Discussionsupporting
confidence: 82%
“…where A diff ¼ 1.12 × 10 10 μm 3 /MPa/s and Q diff ¼ 470 kJ/mol. We showed that the _ ε ref diff values from Equation 3 are comparable to diffusion creep rates of Fe-free olivine and are also consistent with the creep rates predicted from Si grain-boundary self-diffusivity (Fei et al, 2016) (see Figure 14 in Yabe et al, 2020).…”
Section: Olivine Flow Laws Established In Partsupporting
confidence: 80%
See 3 more Smart Citations